(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The research aimed to determine the role of the Syrian Secretariat for Development in supporting education to achieve sustainable development in Lattakia Governorate, in the economic, social, environmental and cultural fields. The research adopted the descriptive approach, and the research community consisted of all the workers in the community centers of the Syrian Secretariat for Development in the province of Lattakia, where the number of community centers (lighthouses) in the province reached (4) lighthouses distributed in the following areas: Sheikh Daher, Al-Saliba, Al-Fakhoura, Al-Qutaylbia. A simple random sample of workers in these community centers was drawn, and it numbered (65) male and female workers, where the questionnaire "research tool" was distributed to them, and (60) complete and valid questionnaires were retrieved for the purposes of statistical analysis. The results of the research showed that the Syrian Secretariat for Development contributes positively to supporting education to achieve sustainable development in the economic, social, environmental and cultural fields. The Syrian Secretariat for Development.